Does residential segregation matter for the labor market performance of immigrants? Evidence from Germany - Sebastian Reil (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
With the arrival of over one million asylum seekers in Germany in 2015, policy discussions opened whether refugees should be spread across the country or spatially concentrated in order to facilitate their integration in society. When an immigrant locates in a residential area with many natives or many foreigners he has access to different respective social networks which are important for the labor market performance. This paper uses the SOEP dataset to estimate which residential location decision via the networks leads to a better labor market performance. Findings show that residential concentration of immigration increases wages of new immigrants, but also raises their unemployment. Native wages are suppressed in an area with many foreigners.
Keywords: 330; migration; residential segregation; labor market